2020
DOI: 10.3390/ph13070150
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Adiponectin Receptor Expression in the 5XFAD Mouse Model of Alzheimer’s Disease

Abstract: Metabolic syndromes share common pathologies with Alzheimer’s disease (AD). Adiponectin, an adipocyte-derived protein, regulates energy metabolism via its receptors, AdipoR1 and AdipoR2. To investigate the distribution of adiponectin receptors (AdipoRs) in Alzheimer’s, we examined their expression in the aged 5XFAD mouse model of AD. In age-matched wild-type mice, we observed neuronal expression of both ARs throughout the brain as well as endothelial expression of AdipoR1. The pattern of receptor expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Amyloid deposition was observed to be greater in old-Tg mice ( Figure 3 i-p) compared to young-Tg mice ( Figure 3 a–h). We had previously reported that 48–52-week-old 5XFAD mice had an increased astrocytic expression of glial fibrillary acidic protein (GFAP) [ 31 ]. Similarly, we observed increased astrocytic GFAP expression in the old-Tg mice ( Figure 3 f–k) compared to young-Tg mice ( Figure 3 c, d).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Amyloid deposition was observed to be greater in old-Tg mice ( Figure 3 i-p) compared to young-Tg mice ( Figure 3 a–h). We had previously reported that 48–52-week-old 5XFAD mice had an increased astrocytic expression of glial fibrillary acidic protein (GFAP) [ 31 ]. Similarly, we observed increased astrocytic GFAP expression in the old-Tg mice ( Figure 3 f–k) compared to young-Tg mice ( Figure 3 c, d).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, to test the effects of Aβ on astrocytes, Allaman et al exposed cultured astrocytes to Aβ 25-35 and found increased glucose metabolism in the cells [54]. Addition of Aβ [25][26][27][28][29][30][31][32][33][34][35] peptides to co-cultures of neurons and astrocytes resulted in impaired neuronal viability. The effect on neurons was abrogated by pre-treatment with PI3K inhibitors, leading the authors to conclude that the deleterious effects were mediated via PI3K signalling [54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Anishchal et al demonstrated that in aged 5XFAD mouse model of AD the pattern of AdipoRs was significantly perturbed. In fact, they have shown a significant decreased expression of both AdipoRs in neurons, as well as a decrease in endothelial cells of AdipoR1, but robust expression of AdipoR2 in activated astrocytes [ 91 ]. They suggest that astrocytes may utilize AdipoR2 signalling to fuel their activated state in the AD Brain [ 91 ].…”
Section: Ceramide and Sphingosine-1-phosphate In Neurodegenerative Di...mentioning
confidence: 99%